2020
DOI: 10.1177/0003489420949588
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Vitamin B2 as a Fluorescent Tracer in Aerosol and Droplet Contamination Models in Otolaryngology

Abstract: Objective: During the COVID-19 era, a reliable method for tracing aerosols and droplets generated during otolaryngology procedures is needed to accurately assess contamination risk and to develop mitigation measures. Prior studies have not investigated the reliability of different fluorescent tracers for the purpose of studying aerosols and small droplets. Objectives include (1) comparing vitamin B2, fluorescein, and a commercial fluorescent green dye in terms of particle dispersion pattern, suspension into ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…A solution of 1 g/L vitamin B2 (riboflavin) in 0.9% normal saline was prepared as fluorescent irrigation. This was found to be a better marker for fine aerosols than fluorescein ( 10 ). For trials that included irrigation, the fluorescent irrigant was applied by an assistant via a squeeze bottle in a pulsatile fashion of about one pulse per second to keep the field appropriately moist.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…A solution of 1 g/L vitamin B2 (riboflavin) in 0.9% normal saline was prepared as fluorescent irrigation. This was found to be a better marker for fine aerosols than fluorescein ( 10 ). For trials that included irrigation, the fluorescent irrigant was applied by an assistant via a squeeze bottle in a pulsatile fashion of about one pulse per second to keep the field appropriately moist.…”
Section: Methodsmentioning
confidence: 98%
“…Generated debris particles with a smaller aerodynamic diameter have a lower tendency to be collected until the final impaction stages. To ensure that the collected aerosols originated from the specimen, Vitamin B2 was used as a fluorescent tracer in the irrigation, coating the entire mastoid drilling surface ( 9 , 10 ). The goals of this study were to objectively characterize whether aerosols of an aerodynamic diameter known to enter the airway are generated during mastoidectomy, map the field contamination of visible debris, and to test aerosol mitigation strategies.…”
mentioning
confidence: 99%
“…Macroscopically visible droplet spread was assessed in six studies, all of which used florescent tracers to map droplet spread [13][14][15][16][17][18] . All of these studies demonstrated that use of a high-speed drill aerosolised droplets outside of the nasal cavity.…”
Section: Macroscopically Visible Dropletsmentioning
confidence: 99%
“…All of these studies demonstrated that use of a high-speed drill aerosolised droplets outside of the nasal cavity. [13][14][15][16][17][18] No detectable droplet spread was detected in two studies considering use of non-powered "cold" instrumentation, 13,14 and one assessing utilisation of an ultrasonic aspirator (UST-2001; Stryker Co., USA). 14 Both Sharma et al (2020) 14 and Leong et al (2021) 15 found that microdebrider use on cadaveric nasal mucosa had the propensity to generate extranasal droplets seen on examination under UV light.…”
Section: Macroscopically Visible Dropletsmentioning
confidence: 99%
See 1 more Smart Citation